Study on the evolution law and stage response relationship between meteorological elements and hydrological drought in Xiangtan area - Wan, Fang; Han, Wenhao; Long, Qiubo; Wang, Weijun; Wang, Guoqing; Zhang, Fei (Frontiers in Environmental Science, 2023)
Studying the propagation law and response relationship between meteorological elements and hydrological drought is conducive to exploring the propagation mechanism and transmission time of drought, and providing a basis for reasonable and efficient drought relief work. In this paper, the area above Xiangtan station is taken as the research area, and the temperature and precipitation are selected as the meteorological elements. The standardized flow index (SDI) is used to characterize the hydrological drought. The linear regression method and Mann-Kendall trend test are used to analyze the evolution sequence of meteorological elements and hydrological drought at different scales. The characteristics and laws of drought propagation are revealed, and the hydrological drought is divided into stages by combining the ordered cluster analysis method and the sliding T test method. The Pearson correlation analysis method is used to analyze the stage correlation degree between meteorological elements and hydrological drought, reflecting the response relationship between meteorological elements and hydrological drought under different types and different scales, and the response period of hydrological drought to meteorological elements at different time scales is obtained. Studying the development trend and evolution law of meteorological elements and hydrological drought, and deeply exploring the phased response relationship are conducive to improving the drought resistance ability and drought disaster reduction management ability of Xiangtan area.